Prayers and healing an interdependent relation - B R Divya; Keshavamurthy (Wolters Kluwer Medknow Publications, 2021)
The human world is realizing and giving importance to prayers and its healing effect throughout the world. In times of natural crisis, public health emergency like COVID 19 pandemic, it has even garnered more attention. There are many evidence based research that proves the benefits of such practices. This paper reviews the effect of prayer and its role in managing, coping and healing during the time of crisis.